Frailty Syndrome: an Emerging Geriatric Syndrome Calling for Its Potential Intervention - Purwita W Laksmi (Acta Medica Indonesiana)
It is projected that the elderly population in Indonesia will increase from approximately 19 million people in 2010 with life expectancy of 69.8 years during period of 2005-2010 to 29 million people in 2020 (11.11% of total population) with life expectancy of 73.6 years during period of 2020-2025. Higher elderly female proportion compared to male (11.43% versus 10.78%) will also be found.1 Aging process happens as people get older. Its process is influenced by genetic and environmental factors that can lead to successful aging, usual (normal) aging or pathologic aging. People with pathologic aging would have an increased risk to become frail.2,3 Nowadays, frailty syndrome is considered as one of the geriatric syndromes which increase the risk of worsening clinical outcome in mobility, functional status, hospitalization, institutionalization and mortality, as well as lower health-related quality of life.4,5 Moreover, frailty syndrome reflects a biological age that predicts mortality risk better than chronological age [RR 1.57 (95% CI 1.41-1.74) versus RR 1.08 (95% CI 1.06-1.2)].6 No wonder, frailty syndrome has attracted clinician’s attention, especially the geriatricians, all over the world with increasing research in this field.